Case of pneumatosis intestinalis and hepatic portal venous gas following a laparoscopic right hemicolectomy. (21st March 2016) - Castren, Edit Elisa; Hakeem, Abdul R; Mahmood, Nabil S; Aryal, Kamal
Abstract : Hepatic portal venous gas (HPVG) in most cases signifies either mechanical migration of air into the portal system due to bowel ischaemia (pneumatosis intestinalis) or portal sepsis due to gas-forming organisms. Successful management of portal sepsis involves early identification of the condition, intensive resuscitation, broad-spectrum antibiotics and a laparotomy for possible bowel ischaemia. In this report, we discuss the case of a patient with pneumatosis intestinalis and HPVG after an elective laparoscopic right hemicolectomy. After an initial slow recovery, on postoperative day seven, the patient had profuse diarrhoea and confusion, and was hyponatraemic. A CT scan revealed pneumatosis intestinalis and HPVG. A laparotomy showed no obvious cause for HPVG and there was no ischaemic bowel. She was managed with intensive care, hyperbaric oxygen therapy, broad-spectrum antibiotics and total-parenteral nutrition. She has made a good recovery. This case highlights the presenting features, differential diagnoses, and management of pneumatosis intestinalis and HPVG.